Role of laryngeal mask airway in laparoscopic cholecystectomy - Beleña, José M (World J Gastrointest Surg, 2015)
Laparoscopic cholecystectomy is one of the most commonly performed surgical procedures and the laryngeal mask airway (LMA) is the most common supraglottic airway device used by the anesthesiologists to manage airway during general anesthesia. Use of LMA has some advantages when compared to endotracheal intubation, such as quick and ease of placement, a lesser requirement for neuromuscular blockade and a lower incidence of postoperative morbididy. However, the use of the LMA in laparoscopy is controversial, based on a concern about increased risk of regurgitation and pulmonary aspiration. The ability of these devices to provide optimal ventilation during laparoscopic procedures has been also questioned. The most important parameter to secure an adequate ventilation and oxygenation for the LMA under pneumoperitoneum condition is its seal pressure of airway. A good sealing pressure, not only state correct patient ventilation, but it reduces the potential risk of aspiration due to the better seal of airway. In addition, the LMAs incorporating a gastric access, permitting a safe anesthesia based on these commented points. We did a literature search to clarify if the use of LMA in preference to intubation provides inadequate ventilation or increase the risk of aspiration in patients undergoing laparoscopic cholecystectomy. We found evidence stating that LMA with drain channel achieves adequate ventilation for these procedures. Limited evidence was found to consider these devices completely safe against aspiration. However, we observed that the incidence of regurgitation and aspiration associated with the use of the LMA in laparoscopic surgery is very low.